Kepentingan Indonesia menjadi Tuan Rumah Pertemuan Tahunan International Monetary Fund (IMF) dan World Bank Group (WBG) tahun 2018 - Sitorus, Rizal Efendi; Putri, Penny Kurnia; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT   This research aims to describe the interests of Indonesia to host the annual meetings of the International Monetary Fund and the World Bank Group in 2018 amidst society rejection and natural disasters that were happening in several regions in Indonesia. The economic sector was a top priority in the national interest of President Jokowi, seen from progressive infrastructure improvement, strengthening tourism sector and MSMEs as well as efforts to attract FDI. However, the benefits of Indonesia are estimated to be not only short-term but also long-term benefits. Therefore, the Researchers used the national interest concept to explain Indonesia’s interest and the place branding concept as the strategy to attain these interests. The research then perceives the answer that Indonesia has four economic interests through tourism sector, MICE industry, investment and infrastructure. Key Words : Annual Meeting, National Interest, Place Branding, Tourism, MICE, Investment, Infrastructure.